Secure Key Exchange and Sessions without Credentials - Canetti, Ran; Kolesnikov, Vladimir; Rackoff, Charles; Vahlis, Yevgeniy (Security and Cryptography for Networks, 2014)
Secure communication is a fundamental cryptographic primitive. Typically, security is achieved by relying on an existing credential infrastructure, such as a PKI or passwords, for identifying the end points to each other. But what can be obtained when no such credential infrastructure is available? Clearly, when there is no pre-existing credential infrastructure, an adversary can mount successful “man in the middle” (MIM) attacks by modifying the communication between the legitimate endpoints. Still, we show that not all is lost, as long as the adversary’s control over the communication is not complete: We present relatively efficient key exchange and secure session protocols that guarantee that any MIM adversary is immediately detected as soon as he fails to intercept even a single message between the legitimate endpoints. To obtain this guarantee we strengthen the notion of key exchange to require that the keys exchanged in any two sessions are independent of each other as long as each session has at least one honest endpoint, even if both sessions has an adversarial endpoint. We call this notion credential-free key exchange. We then strengthen the existing notion of secure session protocols to provide the above guarantee given a CFKE (existing definitions and constructions are insufficient for this purpose). We provide two alternative definitions and constructions of CFKE, a game-based one with a (very efficient) construction in the RO model, and a UC one with a construction in the CRS model.